(untitled) (Journal of Atomic and Molecular Sciences, 2019)
The development of efficient catalysts for the hydrogen evolution reaction (HER) is of extreme importance for future renewable energy systems. In this work, we report on the synthesis of a novel hybrid electrode that boracic nanospheres grown on the top of some NiCo_2O_4 nanowires with nickel foam as the baseboard(B-NiCo_2O_4/NF). Due to this unique structural features, the electrocatalyst has a good activity for HER, which needs overpotential of 150 mV to afford the current density of 10 mA cm^-2, the catalytic activity is maintained for at least 18 h. This work provides a promising methodology for the designing and fabricating highly efficient boracic catalysts for HER.